Kajian TPACK Framework Sebagai Dasar Pengembangan Model Pengembangan Kompetensi Berkelanjutan Bagi Guru - Yoki Ariyana; Aan Komariah; Johar Permana; Asep Suryana (Universitas Negeri Malang, 2025)
Abstract: This study aims to examine the Technological Pedagogical and Content Knowledge (TPACK) framework as a conceptual foundation for developing a Continuous Professional Development (CPD) model for teachers that is adaptive, collaborative, and sustainable. The study employs a qualitative approach using a literature-based research design, drawing on international scholarly articles, policy documents, and research reports published between 2020 and 2025 related to teacher professional development, TPACK, flexible delivery, and learning communities. Data were analyzed using thematic and content analysis to identify key patterns, conceptual gaps, and directions for model development. The findings indicate that effective CPD requires integration of technological, pedagogical, and content knowledge supported by flexible multimodal delivery and professional learning communities to ensure relevance and sustainability. Furthermore, the literature reveals a conceptual gap in existing CPD models, which often overlook the role of teachers’ professional attitudes and character in sustaining pedagogical change. Based on these findings, this study proposes an extended TPACK framework (TPACK-ChA) that integrates attitude and character knowledge as a basis for developing a more comprehensive CPD model for teachers. Keywords: TPACK, CPD, flexible delivery, learning community, teacher professional development. Abstrak: Penelitian ini bertujuan untuk mengkaji kerangka Technological Pedagogical and Content Knowledge (TPACK) sebagai dasar konseptual dalam pengembangan model Pengembangan Kompetensi Berkelanjutan (PKB) bagi guru yang adaptif, kolaboratif, dan berkelanjutan. Penelitian ini menggunakan pendekatan kualitatif dengan desain studi kepustakaan, dengan sumber data berupa artikel jurnal ilmiah internasional, dokumen kebijakan, dan laporan penelitian periode 2020–2025 yang relevan dengan PKB guru, TPACK, pendekatan flexible delivery, dan komunitas belajar. Analisis data dilakukan melalui analisis tematik dan analisis isi untuk mengidentifikasi pola temuan, kesenjangan konseptual, serta arah pengembangan model. Hasil penelitian menunjukkan bahwa PKB yang efektif memerlukan integrasi pengetahuan teknologi, pedagogik, dan konten yang didukung oleh pendekatan multimoda yang fleksibel serta komunitas belajar profesional untuk menjamin keberlanjutan implementasi. Temuan studi literatur juga mengungkap bahwa sebagian besar model PKB belum mengintegrasikan dimensi sikap profesional dan karakter guru secara eksplisit. Berdasarkan temuan tersebut, penelitian ini mengusulkan pengembangan kerangka TPACK yang diperluas dengan integrasi pengetahuan sikap dan karakter (TPACK-ChA) sebagai dasar pengembangan model PKB guru yang lebih komprehensif. Kata kunci: TPACK, PKB, flexible delivery, komunitas belajar, pengembangan profesional guru.